CyberL@bKids: a technology-enhanced language learning resource for primary school children in Costa Rica / CyberL@bKids: un recurso multimedial para el aprendizaje del inglés a nivel de primaria en Costa Rica - Allen Quesada Pacheco (Universidad de Costa Rica, 2013)
This paper makes an analysis of the literature that supports the creation and implementation of CyberL@bKids. CyberL@bKids is a digital platform designed for teaching and learning English according to the curriculum of the Ministry of Education in Costa Rica. It was created by researchers at the University of Costa Rica (UCR), in order to meet the needs of I and II Cycle of public education in the area of English. The design and structure of this digital platform are student-centered. Within this paper, there is a description of the representative colors and characters for each grade (1st to 6th), examples of interactive activities, samples of the presentation of vocabulary, illustrations of the presentation of grammatical structures in context, and examples of the integration of skills, among others. The literature emphasizes the use of meaningful learning strategies, task-based and content-based teaching methods for the teaching and learning of English as a foreign through the integration of technology (ICT). This platform was piloted by the Ministry of Education for a year, and since 2012, CyberL@bKids is used by all primary schools in the country.   Este ensayo hace un análisis de la literatura que sustenta la creación e implementación de CyberL@bKids. CyberL@bKids es una plataforma digital diseñada para la enseñanza y aprendizaje del inglés de acuerdo al currículo del Ministerio de Educación de Costa Rica. La misma fue creada por investigadores de la Universidad de Costa Rica (UCR), con el propósito de cumplir con las necesidades de la educación del I y II Ciclo de Educación Pública en el área de inglés. El diseño y la estructura de esta plataforma digital están centrados en el estudiante. Dentro de este ensayo se describe los colores y personajes representativos para cada grado (primero a sexto grado), ejemplos de actividades interactivas, muestras de la presentación del vocabulario, de las estructuras gramaticales en contexto, y de la integración de destrezas, entre otros. La literatura enfatiza la utilización de estrategias de aprendizaje significativas y métodos de enseñanza basado en tareas y en contenidos auténticos para la enseñanza y el aprendizaje del inglés como lengua extranjera mediada por las TIC. Esta plataforma fue piloteada por el Ministerio de Educación por un año, y a partir del año 2012, es utilizada por todas las escuelas primarias del país.